FUNCTION OF SPECIAL EDUCATOR IN CARRYING OUT INCLUSIVE EDUCATION IN NIGERIA - Josephine. D, Nanjwan; Emmanuel U, Ikwen; Samson A, Aderibgbe; Blessing Bassey, Anam (International Journal of Psychosocial Rehabilitation, 2020)
This paper is on the function of special education personnel in carrying out inclusive education in Nigeria. This paper discussed that inclusive education is connected to regular education innovation. It has been established on the basis that it is more productive for learners with special needs to have diverse’ experiences in social events leading to achievements in life. This paper also analyzed that inclusion entails a drastic meditation of policy and practice and mirrors a basically different way of thinking about the root of learning challenges. Also discussed is the worldwide shift in the carrying out of educational services. This paper presented that the focus of inclusive education is to transform every aspect of human behavior. Children with special needs require major preparation and adaptation. Also discussed are the fundamental steps of inclusive teaching. Personnel here must be prepared in this way. Some suggestions were made as a way forward for inclusive education in Nigeria.